Surviving the Bible: a devotional for the Church year 2020 - Piatt, Christian (Surviving the Bible series, 2019)
Using the annual lectionary as his guide, Christian Piatt has developed a devotional that allows us to read through major parts of the Old and New Testaments. Every week has four Scripture readings, glossary terms, deeper thoughts, and a closing prayer. Start anywhere. Set it down and come back to it. Use it as an in-depth study guide or a daily devotional. There's no ""wrong way"" to use Surviving the Bible